Students' Commognitive Processes in Solving Problem-Based Learning-Oriented Student Worksheets - Zulfah Zulfah; Toto Nusantara; Yusuf Hanafi; Slamet Arifin (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates students’ commognitive processes—the integration of communication and cognition—during problem-based learning (PBL) in mathematics. It is grounded in commognitive theory, which posits that thinking and communication are interdependent. An exploratory descriptive approach was applied at SMA Muhammadiyah Bangkinang, focusing on students in class XI IPA 2. Using purposive sampling, three students representing high, moderate, and low mathematical abilities were selected. Data were collected through written tests, interviews, and documentation. Researcher-developed worksheets and interview protocols, aligned with the four commognitive components—word use, visual mediators, narratives, and routines—were validated by mathematics education experts. Data analysis followed the stages of collection, reduction, presentation, and conclusion drawing. Findings indicate that high-ability students demonstrated more coherent narratives and consistent application of mathematical routines. Conversely, students with moderate and low abilities exhibited fragmented discourse and less effective use of visual mediators and terminology. The study highlights the role of commognitive factors in shaping students' mathematical discourse across ability levels. It suggests that instructional tools designed with commognitive principles can better support the development of mathematical thinking. These insights contribute to understanding the cognitive-communicative dynamics in mathematics education and inform the design of targeted learning interventions. Ethical approval was obtained, and informed consent was secured from all participants.